Comparison of the physical, chemical and electrical properties of ALD Al2O3 on c- and m-plane GaN - Wei, Daming; Hossain, T.; Nepal, N.; Garces, N. Y.; Hite, J. K.; Meyer, H. M. III; Eddy, C. R. Jr.; Edgar, James H. (My University, 2014)
This study compares the physical, chemical and electrical properties of Al[subscript 2]O[subscript 3] thin films deposited on gallium polar c- and nonpolar m -plane GaN substrates by atomic layer deposition (ALD). Correlations were sought between the film's structure, composition, and electrical properties. The thickness of the Al[subscript 2]O[subscript 3] films was 19.2 nm as determined from a Si witness sample by spectroscopic ellipsometry. The gate dielectric was slightly aluminum-rich (Al:O=1:1.3) as measured from X-ray photoelectron spectroscopy (XPS) depth profile, and the oxide-semiconductor interface carbon concentration was lower on c -plane GaN. The oxide's surface morphology was similar on both substrates, but was smoothest on c -plane GaN as determined by atomic force microscopy (AFM). Circular capacitors (50-300 μm diameter) with Ni/Au (20/100 nm) metal contacts on top of the oxide were created by standard photolithography and e-beam evaporation methods to form metal-oxide-semiconductor capacitors (MOSCAPs). The alumina deposited on c -plane GaN showed less hysteresis (0.15 V) than on m -plane GaN (0.24 V) in capacitance-voltage (CV) characteristics, consistent with its better quality of this dielectric as evidenced by negligible carbon contamination and smooth oxide surface. These results demonstrate the promising potential of ALD Al[subscript 2]O[subscript 3] on c -plane GaN, but further optimization of ALD is required to realize the best properties of Al[subscript 2]O[subscript 3] on m -plane GaN.
Keywords: Al[subscript 2]O[subscript 3]; AI2O3; Atomic layer deposition; c- and nonpolar m-plane GaN; c-plane GaN; m-plane GaN